Research Notes - Fottler, Myron D.; Bain, Trevor (Academy of Management Journal, 1980)
The article discusses the role of sex differences in occupational aspirations. According to the results of this study, processes of socialization in the United States at the time of publication encourage occupational aspirations leaning toward professional rather than managerial careers. The study asserts that these processes reinforce existing sex role stereotypes in regards to occupational groupings. Factors labeled by the study that affect occupational aspirations include societal cultural values and the impact of a career on family life.